Climate-Driven Innovations: How Rainfall and Temperature Influence Pasture Technology Adoption in Isiolo County, Kenya - Linus Ireri; Tom Ouna (Eastern African Journal of Humanities and Social Sciences)
Pastoralism is the primary livelihood in Isiolo County's arid and semi-arid regions, but severe droughts and climate change frequently disrupt this way of life, causing food shortages for vulnerable communities. This study explored how pastoralists in Isiolo County adopt Technological, Innovation, and Management Practices (TIMPs) to boost pasture production, reduce land degradation, and enhance resilience to extreme weather. It specifically examined the impact of climatic factors on TIMP adoption, guided by Diffusion of Innovation Theory, which focuses on the adoption process of new technologies. Using a descriptive survey research design, the study sampled 382 heads of households and field extension officers from a population of 48,514. Data was collected through questionnaires, key informant interviews, and Focus Group Discussions (FGDs). A pilot test involving 20 household heads and 1 extension officer was conducted, achieving a reliability coefficient of 0.86 using the Cronbach Alpha formula. Data analysis was performed with Statistical Package for Social Sciences (SPSS) Version 2x, employing Multiple Linear Regression models. The results indicated that temperature had a positive correlation coefficient of 0.791 with TIMP adoption, showing that higher temperatures encourage technology adoption for survival, with a significant effect (p<0.05). Rainfall also had a positive correlation with TIMP adoption, but the relationship was statistically insignificant (p>0.05). Policymakers should therefore prioritize temperature-related interventions and reassess rainfall-related strategies to improve local resilience to extreme climatic conditions.